Genome-wide identification and gene expression analysis of the malate dehydrogenase (MDH) gene family in Eucalyptus grandis - Yifan Xing; Yifan Xing; Huiming Xu; Deming Yang; Lichuan Deng; Guolong Li; Guolong Li; Zhixin Zhao; Zhixin Zhao; Zhaohua Lu; Liuyin Ma; Guangyou Li (Frontiers in Plant Science)
Malate dehydrogenases are pivotal in plant metabolism and stress responses, yet their evolutionary dynamics and functional diversification in woody angiosperms remain underexplored. This study comprehensively characterized the Eucalyptus grandis MDH (EgMDH) gene family to elucidate its roles in development and environmental adaptation. We identified 14 EgMDH genes and conducted phylogenetic, structural, and syntenic analyses to trace their evolutionary origins. Transcriptional networks were deciphered using cis-regulatory element analysis and protein interaction predictions. Spatiotemporal expression under hormone treatments (JA, SA), abiotic stresses (salt, cold), and nutrient deficiencies (phosphate, nitrogen, and boron) was profiled via transcriptome data or RT-qPCR experiments. Phylogenetics revealed three MDH clades: green algal-derived Groups I/II and red algal-derived Group III. Phylogenetics analysis with model plants revealed that Eucalyptus lacked Group III MDHs, while Poplar lacked Group II members, indicating lineage-specific gene loss in woody angiosperms. Four segmental duplicated paralog pairs (EgMDH1/3, 6/9, 10/11, 12/14) exhibited conserved motifs, exon distributions, and synteny with woody dicots, underscoring structural conservation across angiosperms. Sixty transcription factors (TFs) coordinated EgMDH expression, linking them to energy/stress adaptation and secondary metabolism. Subtype-specific regulators (e.g., GT-2, AIL6, NLP6) exclusively targeted Group II EgMDHs, indicating clade-divergent regulatory networks. EgMDHs showed tissue- and stage-dependent expression, particularly during late adventitious root development. EgMDH genes also exhibited temporally distinct expression patterns under JA treatment, SA treatment, salt stress and cold stress conditions. Notably, eleven EgMDH proteins interacted with PPC1/ASP3, coupling malate metabolism to nitrogen/phosphate homeostasis and C/N balance. Taken together, EgMDH genes displayed phased temporal and tissue-specific expression under Pi/N/B deficiencies. These results revealed that coordinated transcriptional reprogramming and protein interactions of EgMDHs were critical for nutrient stress adaptation. Overall, this study suggested that EgMDH genes underwent lineage-specific diversification and played important roles in development and stress resilience.